DEVELOPMENT OF A MODEL REPRESENTATION OF COMPETENCIES IN EDUCATION PROJECT - Алексей Евгеньевич КОЛЕСНИКОВ; Дмитрий Владимирович ЛУКЬЯНОВ; Валентина Юльевна ВАСИЛЬЕВА (Вісник Національного технічного університету «ХПÌ». Серія: Стратегічне управління, управління портфелями, програмами та проектами, 2016)
Value orientation of education is to expand its accessibility and the creation of a system of continuous education in the form of automated learning systems. A solution of the problem of individualization of learning is only possible in the case of competence approach allows you to structure the courses in the form of a minimum set of educational elements that form the basic knowledge and skills of students. To form the competencies necessary to make a set of disciplines, with mandatory release of interdisciplinary connections. Formation of competencies takes place on the basis of not only the relationship between the disciplines, and the general knowledge of the subject area. The paper deals with the structural model of relations between the competencies of the national standard in Ukraine. It is shown that the relationship between the competencies objectively exist and can be used for the formation of a set of competencies for which all the elements are interconnected and thus form a set of interrelated elements - the core of competencies.